Development of Medicinal Plant Conservation Area Based on Local Wisdom of Mapur Indigenous Community - Syuraya Faradis; Prada Sari; Suci Dwi Anggia; Adi Indra Saputra; Nova Saputri; Noveni Delianti; Pariza Patilawati; Ramadhon Ramadhon; Sekar Kinanti Ramadhini Naswanto; William Fauzhi Gunzhales; Yuristian Yuristian; Gigih Ibnu Prayoga (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
Air Abik Hamlet has abundant natural resources, especially medicinal plants. The population of medicinal plants will decrease if there is no effort to maintain the medicinal plants. The unavailability of a learning platform regarding efforts to preserve or conserve medicinal plants is one of the factors that become an obstacle in increasing public awareness of the importance of medicinal plant conservation to be carried out. This service aims to preserve medicinal plants typical of the Mapur custom through sustainable conservation activities and develop medicinal plant products that produce so that they can help realize a more advanced Air Abik Hamlet. The results of the service show that the background of the emergence of the medicinal plant conservation program is by looking at the potential of medicinal plants that must be maintained so that they are not lost and can be used as a business to improve the community's economy. The results of the program include the formation of in-situ and ex-situ conservation areas, a map of the distribution of medicinal plants, more innovative product packaging, and the formation of herbal medicine cafes are the basic stages for the service program so that program sustainability is still needed to develop conservation areas and patent medicinal plant products in Air Abik Hamlet.